The Montreal Olympics : an insider's view of organizing a self-financing games - Howell, Paul Charles (McGill-Queen's University Press, 2009)
The 1976 Montreal Summer Olympics were the riveting games the world had ever seen. This title offers an insider's perspective on how this complex, expensive, and politicized event was organized within the constraints imposed by limited resources, an unyielding deadline, and intense pressures from international and local special interest groups.